The impact of diverging economic structure on current account imbalances in the euro area - Philipp Ehmer (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2014)
The measures implemented to reduce current account deficits within several euro area econ-omies are aimed at boosting competitiveness to raise exports. Due to low industrial capacities in Greece, Portugal and Spain, for instance, it is questionable, however, whether exports can contribute much to the required turnaround of the current account. The existing literature on current account determinants ignores the impact of economic structure. However, as industrial goods are more tradable than services, a specialisation on manufacturing industries should ceteris paribus lead to an improved current account. The empirical analysis of this paper con-firms a significant impact of the sectoral focus on the current account within the euro area. Hence, the turnaround in crisis-hit economies has to be accomplished mostly through imports. As can be observed, this brings about severe recessions - more severe than in manufacturing-based economies which use the exports channel to a larger extent. Within a currency union where there is no depreciation which facilitates the adjustment economies should aim at har-monising their economic structure regarding export capacity.
Keywords: E21; F32; F41; L16; O14; 330; euro area; current account imbalances; current account determinants; savings rate; economic structure; sectoral focus; optimum currency area